The relational view revisited - Dyer, Jeffrey H.; Singh, Harbir; Hesterly, William S. (Strategic Management Journal, 2018)
[Research Summary: This paper extends the relational view to offer a dynamic perspective on the factors that drive value creation and value capture over the alliance life cycle. We argue that access to complementary resources provides an initial rationale for forming alliances, but benefits from complementarity can attenuate over time. Indeed, viewed dynamically, factors that often lead to higher value creation—informal trust, repeated ties, customized assets—may also lead to diminished alliance performance. We highlight interdependence between the complementary resources of partners as the critical factor determining the pattern of alliance value creation, notably how quickly alliances generate value and how quickly they are likely to dissolve. We identify factors, both internal and external to the alliance, that trigger diminished value creation and increased competition for value capture among partners. Managerial Summary: The “relational view” perspective has shown that firms create value in alliances when they identify partners with complementary resources, when they build high levels of informal trust and they share knowledge and make investments that are customized to the partner. The level of resource interdependence in alliances determines how quickly alliances can reach their potential in value creation and how quickly they are likely to dissolve. Viewed dynamically, factors that often lead to higher value creation—like informal trust, repeated ties, customized assets—may also lead to diminished alliance performance. Finally, a number of factors both internal to and external to an alliance may trigger competition between the partners within an alliance to capture the value created by the alliance and also diminish the value created within the alliance.]